The Ecological Assessment of Responses to Speaking-up tool—development and reliability testing of a method for coding safety listening behavior in naturalistic conversations - Pandolfo, Alyssa M.; Reader, Tom W.; Gillespie, Alex (Frontiers in Public Health, 2025)
IntroductionSafety communication is crucial for accident aversion across industries. While researchers often focus on encouraging concern-raising (‘safety voice’), responses to these concerns (‘safety listening’) remain underexplored. Existing studies primarily use self-report measures; however, these tend to focus on perceptions of listening rather than behaviors. To fully understand and examine how safety listening is enacted and influential in safety-critical environments, a tool for reliably assessing naturalistic safety listening behaviors in high-risk settings is required. Accordingly, we developed and tested the Ecological Assessment of Responses to Speaking-up (EARS) tool to code safety listening behaviors in flightdeck conversations.MethodsThere were three analysis phases: (1) developing the taxonomy through a qualitative content analysis (n = 45 transcripts); (2) evaluating interrater reliability and coder feedback (n = 40 transcripts); and (3) testing the taxonomy’s interrater reliability in a larger unseen dataset (n = 110 transcripts) and with an additional coder (n = 50 transcripts).ResultsContrary to the notion that effective listening is agreement, our findings emphasize engagement with safety voice, including reasonable disagreement. The final taxonomy identifies six safety listening behaviors: action (implementing, declining), sensemaking (questioning, elaborating), and non-engagement (dismissing, token listening) and two additional voice acts (escalating, amplifying). EARS achieved substantial interrater reliability (Krippendorff’s alpha of 0.73 to 0.77 and Gwet’s ACT1 of 0.80 to 0.87).DiscussionThe EARS tool allows researchers to assess safety listening in naturalistic conversations, facilitating analysis of its antecedents, its interplay with safety voice, and the impact of interventions on outcomes.